1993
DOI: 10.1007/bf00315306
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of H2 receptor antagonist ? piroxicam coadministration in patients with joint disorders

Abstract: A randomised crossover study was performed in subjects with rheumatoid arthritis (or other arthropathies) to investigate if any alteration in the steady pharmacokinetics of the NSAID piroxicam (a drug which is extensively metabolised via cytochrome P450) or its major metabolites occurred as a result of coadministering either cimetidine or nizatidine. Twelve females and 2 males with mean age, weight, and albumin concentrations of 58 years, 61 kg, and 40 g.L-1 respectively, completed the study. Comparisons were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For dissolution studies, the samples were tested with the dispersed amounts method (17) by placing 10 mg of piroxicam or its equivalent in coprecipitates or in physical mixtures on the surface of the dissolution medium. Aliquots (5 mL) were withdrawn at 2, 4,6,8,10,15,20,30,40, and 60 min and replaced with 5 mL of fresh dissolution medium. The amounts of piroxicam in dissolution media pH 1.2 and pH 4.0 were determined using UV spectroscopy at 344 and 356 nm, respectively.…”
Section: Dissolution Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For dissolution studies, the samples were tested with the dispersed amounts method (17) by placing 10 mg of piroxicam or its equivalent in coprecipitates or in physical mixtures on the surface of the dissolution medium. Aliquots (5 mL) were withdrawn at 2, 4,6,8,10,15,20,30,40, and 60 min and replaced with 5 mL of fresh dissolution medium. The amounts of piroxicam in dissolution media pH 1.2 and pH 4.0 were determined using UV spectroscopy at 344 and 356 nm, respectively.…”
Section: Dissolution Studiesmentioning
confidence: 99%
“…According to some studies, the coadministration of cimetidine and piroxicam does not impair the efficacy of piroxicam or cause any adverse effects (8) but can increase the plasma concentrations of piroxicam (9). Recent studies have demonstrated that coprecipitation of cimetidine and piroxicam at a 1:1 mole ratio can transform the crystalline structures of both drugs to an amorphous state (manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…In a small study in patients with joint disorders comparing the consequences of coadministration of the H2-receptor antagonists cimetidine and nizatidine with piroxicam, no clinically significant alteration in the steady-state pharmacokinetics of piroxicam occurred. [80] The AVC of salicylic acid is not altered by cimetidine or ranitidine.l 42 )…”
Section: Histamine H2-receptor Antagonistsmentioning
confidence: 98%
“…The concomitant administration of cimetidine and piroxicam does not result in any impairment of the efficacy of piroxicam, or cause any adverse effect (8), but co-administration of cimetidine can result in an increase in the plasma concentrations of piroxicam (9). The preparation of binary mixtures of some drugs has been reported to be accompanied by a change in the crystalline structures of the starting drugs (10,11).…”
Section: Introductionmentioning
confidence: 99%